A Middle Aged Man Presented with Recurrent Hypokalaemia and Basal Ganglia Calcification - Das, Aparna; Sultana, Rabab; Kahhar, MA (Journal of Medicine, 2016)
Abstract not available J MEDICINE January 2016; 17 (1) : 57-58